Preaxial polydactyly following early gestational exposure to the smoothened agonist, SAG, in C57BL/6J mice. Issue 1 (20th January 2017) - Fish, Eric W.; Parnell, Scott E.; Sulik, Kathleen K.; Baker, Lorinda K.; Murdaugh, Laura B.; Lamson, David; Williams, Kevin P.
Abstract : Background: While pharmacological activation of the Hedgehog (HH) signaling pathway may have therapeutic benefits for developmental and adult diseases, its teratogenic potential is of concern. The membrane molecule Smoothened (SMO) transduces HH signaling and can be acutely modulated by antagonists and agonists. The objective of the current experiments was to determine how maternal treatment with the Smo agonist, SAG, affects the developing limb. Methods: Pregnant C57BL/6J mice received a single injection of SAG (15, 17, or 20 mg/kg, i.p.) or its vehicle on gestational day (GD) 9.25, the time of limb bud induction. Embryos were examined on GD 15 for gross dysmorphology and skeletal staining was performed to visualize the number and type of digits on the fore‐ and hindlimbs. Additionally, in situ hybridization was performed 4 hr after GD 9.25 SAG administration to determine SAG's effects on Gli1 and Gli2 mRNA expression. Results: The most prevalent effect of SAG was the dose‐dependent induction of pre‐axial polydactyly; defects ranged from a broad thumb to the duplication of two finger‐like digits on the preaxial side of the thumb. The highest SAG dose was effective in ca. 80% of the embryos and increased Gli1 and Gli2 mRNA expression in the limb bud, with Gli1 mRNA being the most upregulated. Conclusion: Preaxial polydactyly can be caused in the developing embryo by acute maternal administration of a Smo agonist that activates HH signaling. These results are consistent with the preaxial polydactyly induced in developmental disorders associated with mutations in HH signaling genes.Birth Defects Research 109:49–54, 2017. © 2016 Wiley Periodicals, Inc.